Qualidade fisiológica de sementes de sorgo armazenadas, recobertas com silício. - Bezerra, Maria Jayane Mota (2016)
The storage capacity of the seeds of a species or cultivar depends on the factors that define the quality of the seeds and environmental storage conditions. Seed coating is a highly efficient technology in protecting seeds, and is being used increasingly to provide great advantages to the farmer. The aim of this study was to evaluate the physiological quality of sorghum seeds coated with silicon for storage. The experiment was conducted in seed analysis laboratory (LAS) belonging to the Federal University of Ceará, during the period from December / 2014 to December / 2015. Doses were tested: D0-0 (control), D1- 100, D2-200, D3-300 and D4- 400 g of silicon per 100 kg of seed for the seed quality during six months of storage and in two environments, cold storage and natural condition. The evaluations were performed every two months, a total of seven. The variables analyzed were: water content (TA), germination percentage (PG), accelerated aging (EA), electrical conductivity (EA), emergence speed index (ESI), shoot length (CPA), length root (CR), and total dry matter (PMST). The experimental design was completely randomized with factorial 7 x 5 ( storage period x silicon dose) with four replications , the data were run separately for each environment ( cold, natural condition Chamber ) with four replications with four replications. According to the results, we conclude that the cold room storage is the most suitable environment to maintain the physiological quality of sorghum seeds and the use of silicon in the coating did not affect the quality of stored seeds